Effectiveness of nationwide programmatic testing and treatment for latent tuberculosis infection in migrants in England: a retrospective, population-based cohort study - Luis C Berrocal-Almanza, PhD; Ross J Harris, PhD; Simon M Collin, PhD; Morris C Muzyamba, PhD; Olivia D Conroy, MSc; Adil Mirza, MSc; Anne-Marie O'Connell, MSc; Lynn Altass, MSc; Sarah R Anderson, MD (Res); H Lucy Thomas, MD; Colin Campbell, MD; Dominik Zenner, MD; et al. (Elsevier, 2022)
Summary: Background: In low-incidence countries, tuberculosis mainly affects migrants, mostly resulting from reactivation of latent tuberculosis infection (LTBI) acquired in high-incidence countries before migration. A nationwide primary care-based LTBI testing and treatment programme for migrants from high-incidence countries was therefore established in high tuberculosis incidence areas in England. We aimed to assess the effectiveness of this programme. Methods: We did a retrospective, population-based cohort study of migrants who registered in primary care between Jan 1, 2011, and Dec 31, 2018, in 55 high-burden areas with programmatic LTBI testing and treatment. Eligible individuals were aged 16-35 years, born in a high-incidence country, and had entered England in the past 5 years. Individuals who tested interferon-γ release assay (IGRA)-negative were advised about symptoms of tuberculosis, whereas those who tested IGRA-positive were clinically assessed to rule out active tuberculosis and offered preventive therapy. The primary outcome was incident tuberculosis notified to the national Enhanced Tuberculosis Surveillance system. Findings: Our cohort comprised 368 097 eligible individuals who had registered in primary care, of whom 37 268 (10·1%) were tested by the programme. 1446 incident cases of tuberculosis were identified: 166 cases in individuals who had IGRA testing (incidence 204 cases [95% CI 176-238] per 100 000 person-years) and 1280 in individuals without IGRA testing (82 cases [77-86] per 100 000 person-years). Overall, in our primary analysis including all diagnosed tuberculosis cases, a time-varying association was identified between LTBI testing and treatment and lower risk of incident tuberculosis (hazard ratio [HR] 0·76 [95% CI 0·63-0·91]) when compared with no testing. In stratified analysis by follow-up period, the intervention was associated with higher risk of tuberculosis diagnosis during the first 6 months of follow-up (9·93 [7·63-12·9) and a lower risk after 6 months (0·57 [0·41-0·79]). IGRA-positive individuals had higher risk of tuberculosis diagnosis than IGRA-negative individuals (31·9 [20·4-49·8]). Of 37 268 migrants who were tested, 6640 (17·8%) were IGRA-positive, of whom 1740 (26·2%) started preventive treatment. LTBI treatment lowered the risk of tuberculosis: of 135 incident cases in the IGRA-positive cohort, seven cases were diagnosed in the treated group (1·87 cases [95% CI 0·89-3·93] per 1000 person-years) and 128 cases were diagnosed in the untreated group (10·9 cases [9·16-12·9] per 1000 person-years; HR 0·14 [95% CI 0·06-0·32]). Interpretation: A low proportion of eligible migrants were tested by the programme and a small proportion of those testing positive started treatment. Despite this, programmatic LTBI testing and treatment of individuals migrating to a low-incidence region is effective at diagnosing active tuberculosis earlier and lowers the long-term risk of progression to tuberculosis. Increasing programme participation and treatment rates for those testing positive could substantially impact national tuberculosis incidence. Funding: National Institute for Health Research Health Protection Research Unit in Respiratory Infections.